Indigenous representation images and words in Peru of the twentieth century : Martín Chambi´s pictures and José María Arguedas' essays - Núñez Murillo, Gabriela (2017)
The purpose of this article is to compare the written discourse of the writer JoséMaría Arguedas (1911-1969) and the photographs of Martín Chambi (1891-1973) in order to analyze the representation of Peruvian indigenous in the 20th century. These two authors have been chosen because, each one of them in their communicative media, are emblematic to the understanding of indigenous identity in Peru. Although the production of Chambi occurs at the beginning of the 20th century and that of Arguedas is a little later, both authors shared the same historical period and were embedded in the Andean culture. Besides, both not only represented the indigenous as a different one from them, like indigenismo movement traditionally did, but were to some extent, actors of their discursive representations. Both artists were aware of the privileged situation of belonging to two different worlds. Chambi, from indigenous origin, had access to the circles of the intellectual elite who appreciated his work; Arguedas, who belonged to a mestizo family from Andahuaylas, had the fortune of being raised by indigenous settlers. In this article it is considered three examples to illustrate how the representation of the indigenous subaltern in the work of these authors, gives an agency to the indigenous people that they had not had before.